REALISASI MULTI TRACK DIPLOMACY PADA PERAN â€œ1000 ABRAHAMIC CIRCLES PROJECTâ€ DALAM MENCIPTAKAN PERDAMAIAN ANTAR UMAT BERAGAMA - Aini, Rezki Putri Nur (UIN Walisongo Semarang, 2019)
This research aims to explain about how the realization of multi track diplomacy on the role of ?1000 Abrahamic Circles Projects? as the main concept idea in creating ideals of peace between religious communities in the world. In order to create harmony between religious communities in the world, especially in the three Abrahamic religions (Islam, Christian, and Jews). It is necessary to have a concept idea as a bridge to uniting different views because of their diversity in beliefs. This phenomena become the moral responsibility of Indonesia as the largest Muslim majority country in the world to participate in achieving peace. According to Dino Pati Djalal as the founder of Foreign Policy of Community of Indonesia and the initiator of ?1000 Abrahamic Circles Projects?, the tension and negativity between each of adherents the religion is higher. So, that we need a program that targeting the grassroots as a basic aspect of nature forming a change of thought in adherent overall. This diplomacy step taken by Dino represented individually through NGOs that Indonesia?s identity as a Muslim majority country which was quite tolerant in dealing with religious communities and concerned in the process of creating world peace by offering various strategies and diplomacy. In addition, as a Muslim, he initiated a form of diplomacy conducted by his NGOs as an arbitrator to overcome these problems. This paper will analyze one of the types of diplomacy realization carried out by a non-state actor and aims to create world peace, especially among the three religious communities with interesting ideas, ?1000 Abrahamic Circles Projects? where in each circle will be facilitated by a trained interfaith dialogue facilitator and local guide so the process of improving relations is not just delivering speeches on certain stages, but should be begin by getting to know each other.